Strengthening Educational Access for Vulnerable Children: A Policy Analysis of Local Government Initiatives in West Nusa Tenggara - M. Ahleyani; Widi Astuti, Irma; Aulia, Syifa (Journal of Society Bridge, 2025)
This research analyzes the role of local governments in Nusa Tenggara Barat (NTB) in increasing access to education for children from vulnerable families. Drawing on policy reviews, interviews with local officials, and field observations in selected districts, the study finds that while programs such as BOSDA, PIP, and community-based scholarships have improved enrollment rates, structural barriers persist, such as child labor, lack of school transportation, and weak inter-sectoral coordination. The paper recommends targeted interventions through village-based budgeting, data-driven social protection, and strengthening public–private partnerships to ensure inclusive and sustainable access to education.